Students' Experience in Using Lesson Study in Microteaching Class at the English Department of Universitas Negeri Padang - Putri Wahyuni; Yuli Tiarina (Universitas Negeri Padang, 2020)
AbstractWahyuni, Putri. (2020). Students’ Experience in Using Lesson Study in Microteaching Class at English Department of Universitas Negeri Padang. Thesis. Padang: English Language and Literature Department. Faculty of Languages and Arts. Universitas Negeri Padang. Lesson Study is a learning improvement system originating from Japan. It is a new innovation in Microteaching classes to help students work collaboratively in the English Department of UNP. The purpose of this research is to find out students’ experience in using Lesson Study in Microteaching class. The population of this research is the third year students of the English Department, Universitas Negeri Padang. There were 70 students taken through purposive sampling as the sample. The instrument of this research was a questionnaire and interview to support the data. The questionnaire consisted of 54 questions and divided into four stages; Plan, Observation, Reflection, and Profit. The experience of the students in using Lesson Study was categorized into a negative experience, moderate, and positive experience. To support the data questionnaire the researcher made a description from the data interview. The result shows that the students’ experience in using Lesson Study is a positive experience. This fact was supported by the students’ mean score was 3,76 indicates a positive experience. The difficulty felt by the students was in the observation stage, and the most helpful stages were the reflection stage. Keywords: Experience, Lesson Study, Microteaching